Analysis of Antigen‐Specific Human Memory B Cell Populations Based on In Vitro Polyclonal Stimulation. (5th October 2020) - Nguyen‐Contant, Phuong; Embong, A. Karim; Topham, David J.; Sangster, Mark Y.
Abstract: Antigen‐specific memory B cell (MBC) populations mediate the rapid, strong, and high‐affinity secondary antibody responses that play a key role in combating infection and generating protective responses to vaccination. Recently, cell staining with fluorochrome‐labeled antigens together with sequencing methods such as Drop‐seq and CITE‐seq have provided information on the specificity, phenotype, and transcriptome of single MBCs. However, characterization of MBCs at the level of antigen‐reactive populations remains an important tool for assessing an individual's B cell immunity and responses to antigen exposure. This is readily performed using a long‐established method based on in vitro polyclonal stimulation of MBCs to induce division and differentiation into antibody‐secreting cells (ASCs). Post‐stimulation antigen‐specific measurement of the MBC‐derived ASCs (or the secreted antibodies) indicates the size of precursor MBC populations. Additional information about the character of antigen‐reactive MBC populations is provided by analysis of MBC‐derived antibodies of particular specificities for binding avidity and functionality. This article outlines a simple and reliable strategy for efficient in vitro MBC stimulation and use of the ELISpot assay as a post‐stimulation readout to determine the size of antigen‐specific MBC populations. Other applications of the in vitro stimulation technique for MBC analysis are discussed. The following protocols are included. © 2020 Wiley Periodicals LLC Basic Protocol 1 : Polyclonal stimulation of memory B cells using unfractionated PBMCs Alternate Protocol : Stimulation of small PBMC numbers using 96‐well plates with U‐bottom wells Basic Protocol 2 : ELISpot assay for enumeration of memory B cell−derived antibody‐secreting cells